Problematic of the Valorization of Solid Waste in The City of Porto-Novo In Benin - DANSOU, Brice Saturnin; ODOULAMI, Léocadie (My University, 2018)
Waste management represents not only a fundamental ecological challenge for the city of PortoNovo but also a socio-economic opportunity because it creates jobs. This study analyzes waste recovery strategies implemented in the city of Porto-Novo. The socio-economic data on the forms of recovery of waste as well as the benefits resulting from waste recovery were collected from 600 households surveyed. They were stripped and then processed using the tools of descriptive statistics. They are then supplemented by interviews with 42 resource persons as well as information on the experiences of waste recycling in the world. The results show that in the city of Porto-Novo, two possibilities for recovery are offered to the waste when they are not directed towards a final discharge (controlled or not). This involves material recovery (reuse, recycling reuse) and energy recovery. These strategies are small-scale and do not allow populations to benefit significantly from their wastes. The appropriation of waste recycling experiments in Benin and in the world is essential for integrated waste management in the city of Porto-Novo.
Keywords: Benin; Porto-Novo city; valorization; waste